2012
DOI: 10.1002/jccs.201100635
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Immersion System for Peptide Enrichment

Abstract: A complementary peptide separation and purification system, using a novel, artificial, affinity-type extraction material, is described. Cellulose paper was first coated with a 3-methacryloxypropyltrimethoxysilane (MPS) layer, followed by imprinting with peptides, to form an approximately 2-µm layer of film (molecularly imprinted polymer film; MIPF) on both sides and resulted in an increased affinity toward the corresponding template as well as to matched polypeptides. MIPF-cellulose paper (MIFC) was immersed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This has to take in account many different interactions, simultaneously occurring around the template molecule, and the template insolubility into organic solvents generally used for the polymeric synthesis [26][27] . However, several MIPs have been developed for peptide enrichment and employed in the sample preparation of proteomic workflows [28][29][30][31][32][33][34][35] .…”
Section: Introducionmentioning
confidence: 99%
“…This has to take in account many different interactions, simultaneously occurring around the template molecule, and the template insolubility into organic solvents generally used for the polymeric synthesis [26][27] . However, several MIPs have been developed for peptide enrichment and employed in the sample preparation of proteomic workflows [28][29][30][31][32][33][34][35] .…”
Section: Introducionmentioning
confidence: 99%
“…Then, 200 µl of the supernatant was taken out and measured using a Fluorescence Microplate Reader at E ex / E em = 290 nm/350 nm. The binding affinities of PCIMPs were evaluated using the Scatchard analysis equation ( 1 ) ( Gerdon et al, 2005 ; Diltemiz et al, 2009 ; Tai et al, 2012 ; Kanubaddi et al, 2021 ), …”
Section: Methodsmentioning
confidence: 99%
“…The PCIMPs-grafted 15-and 14-mer peptides were then tested for their ability to bind their mother protein, as described previously (Tai et al, 2012). As shown in Table 2, it was found that PCIMPs 65-79 had more significant binding affinities, while the other two, PCIMPs [65][66][67][68][69][70][71][72][73][74][75][76][77][78] and PCIMPs 66-79 , exhibited lower affinity.…”
Section: Fabrication Of Pcimps To Capture Papmentioning
confidence: 99%
“…Then, 200 µL of supernatant was collected and measured by Fluorescence Microplate Reader at λex/λem = 290 nm/350 nm. Each experiment was repeated three times, and the results of the binding studies were evaluated using the Scatchard Equation (1) [ 27 , 28 , 29 ]. [RL]/[L] = (B max − [RL])/K d where [L] is the concentration of PPT in the solution, [RL] is the concentration of bound PPT, B max denotes the maximum number of binding sites, and K d is the dissociation constant of the ligand.…”
Section: Methodsmentioning
confidence: 99%
“…Then, 200 µL of supernatant was collected and measured by Fluorescence Microplate Reader at λex/λem = 290 nm/350 nm. Each experiment was repeated three times, and the results of the binding studies were evaluated using the Scatchard Equation (1) [27][28][29].…”
Section: Determination Of Binding Affinities Of Pcimpsmentioning
confidence: 99%